2017
DOI: 10.1111/crj.12738
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and quality of life in patients with moderate to very severe chronic obstructive pulmonary disease

Abstract: In conclusion, irrespective of OSA, patients with COPD are suffering from poor sleep quality and poor sleep quality negatively affects the QoL. Also, COPD and OSA association causes worsened vitality in the terms of health-related QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 32 publications
4
28
3
2
Order By: Relevance
“…Previous studies have reported about sleep problems in patients with COPD using COPD‐specific and non‐COPD‐specific measures. The majority of sleep studies in patients with COPD have relied on two non‐disease specific measures, that is, the Pittsburgh Sleep Quality Index and/or the Epworth Sleep Scale 16,17 . These generic measures, which cover broadly defined domains such as functional status and perceptions, may not perform well in specific populations 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported about sleep problems in patients with COPD using COPD‐specific and non‐COPD‐specific measures. The majority of sleep studies in patients with COPD have relied on two non‐disease specific measures, that is, the Pittsburgh Sleep Quality Index and/or the Epworth Sleep Scale 16,17 . These generic measures, which cover broadly defined domains such as functional status and perceptions, may not perform well in specific populations 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sleep problems in patients with COPD using COPD‐specific and non‐COPD‐specific measures. The majority of sleep studies in COPD have relied on two non‐disease‐specific measures, that is, the Pittsburgh Sleep Quality Index and/or the Epworth Sleep Scale . These generic measures, which cover broadly defined domains such as functional status and perceptions, may not perform well in patients with COPD considering no data of reliability or validity tests to justify their use in this population .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not correct to conclude that the improvement in gas exchange is responsible for all of the clinically relevant improvements achieved, as the relationship between gas exchange parameters and HRQoL for example is very limited. Effects such as improvement in sleep quality and sputum clearance, and a reduction in exacerbation rate probably all act positively on HRQoL [ 40 , 65 , 66 ].…”
Section: Challenges In Noninvasive Ventilationmentioning
confidence: 99%